Judicial Reasoning in the Sentencing of the Maba Sangaji Indigenous Community for Obstruction of Mineral and Coal Mining Activities: A Study of Decision Number 108/Pid.Sus/2025/Sos - Muchammad Husein Rifai (Universitas Islam Negeri Raden Intan Lampung, 2025)
Mining conflicts often place indigenous communities in a vulnerable position when objections to ecological degradation are criminalized as obstruction of lawful business activities. This article examines the judicial reasoning in Decision Number 108/Pid.Sus/2025/Sos, evaluates its consistency with Anti-SLAPP principles, indigenous peoples’ rights, and the right to a healthy environment, and formulates a more appropriate model of legal protection. This study applies normative-prescriptive legal research using statutory and case approaches. The data consist of primary legal materials, including mining, environmental, constitutional, and judicial instruments, PERMA Number 1 of 2023, Constitutional Court Decision Number 119/PUU-XXIII/2025, and secondary materials on mining governance, indigenous communities, environmental defenders, and ecological justice. The findings reveal that the court’s reasoning remained formalistic by emphasizing the interruption of PT Position’s operations, while insufficiently assessing ecological context, customary land, Sangaji River pollution, and public participation. The article recommends a judicial policy requiring Anti-SLAPP assessment in mining cases involving indigenous communities.